The Role of Leisure Satisfaction in Serious Leisure and Subjective Well-Being: Evidence From Chinese Marathon Runners - Tian, Hai Bo; Qiu, Ya Jun; Lin, Ye Qiang; Zhou, Wen Ting; Fan, Chu Yao (Frontiers in Psychology, 2020)
The topics of serious leisure and subjective well-being have been discussed extensively in previous research. It is generally acknowledged that people prefer to experience deeper satisfaction and happiness by participating in serious leisure activities. However, it is essential to examine the relationship between serious leisure and subjective well-being in an urban setting as well as the mediating effect of leisure satisfaction. Data were collected from 447 recreational runners at the 2018 Wuxi International Marathon event in China. The study results showed that serious leisure was positively associated with leisure satisfaction and subjective well-being, leisure satisfaction was positively associated with subjective well-being, and leisure satisfaction completely mediated the relationship between serious leisure and subjective well-being. These results help explain the intricate relationship between serious leisure and subjective well-being and offer theoretical and managerial implications for serious leisure.